UPAYA PENCEGAHAN DAN KESIAPSIAGAAN MASYARAKAT TERHADAP TANGGAP DARURAT BENCANA GEMPA BUMI DAN TSUNAMI (Studi Kasus Di Kecamatan Kolono Timur Kabupten Konawe Selatan) - Erny Tamburaka; Osu Oheoputra Husen (Jurnal Akrab Juara, 2019)
Disaster prevention and community preparedness have a significant and strong influence on earthquake and tsunami disaster response in East Kolono sub-District, South Konawe Regency with an R2 value of 0.888, which means prevention and public preparedness have an effect of around 88.80% on disaster response earthquake and tsunami. Partially, prevention has a significant and strong influence on earthquake and tsunami disaster response,and community preparedness also have a significant and strong influence on the earthquake and tsunami disaster response in East Kolono sub-District. In the management of earthquake and tsunami disaster response in the eastern sub-district of East Kolono, it is carried out by making routes and evacuation sites, where there are eleven 11 potential and feasible temporary evacuation locations in Ngapawali Village for 2 points; Batu Putih Village 3 points; 2 points of Rumba-Rumba Village, 2 points of Ampera Village and 2 points of Amolengu Village, and 9 main points of evacuation, namely in Ngapawali Village 1 point, Batu Putih Village 2 points, Rumba-Rumba Village 2 points, Ampera Village 2 points, and Amolengu Village 2 points.